TEN YEARS OF BIOLOGICAL INVESTIGATIONS OF THE SOVIET ANTARCTIC EXPEDITION (1956-1966) - Andriyashev, A. P. (1967)
The work was performed in accordance with a broad complex program designed for the study of plankton, bottom-dwelling invertebrates and fish of the continental shelf and of abysmal depths; collections and observations of birds, seals and cetatians, surface and fresh-water flora and fauna were carried out on a more limited scale; parasitological and microbiological investigations and determinations of diurnal production of organic matter on the basis of radioactive carbon were performed during some of the cruises. Desyat Let Biologicheskikh Issledovanii Sovetskoi Antarkticheskoi Ekspeditsii (1956-1966), trans. of Sovetskaya Antarkticheskaya Ekspeditsiya. Informatsionnyi Byulleten (USSR) n57 p120-7 1966.